SELF-CARE BAGI KONSELOR YANG BERADA DALAM TEKANAN MENGGUNAKAN TERAPEUTIK - Joice Stella Mamesah; Randy A. A. P. Lombogia (Institut Agama Kristen Negeri Manado, 2023)
In pastoral counseling, a counselor has the task of helping clients face their problems. Many counselors have to deal with many clients with very diverse problems, even very complicated problems and also have to deal with the counselor's own personal problems. So based on this, Sometimes counselors are under pressure which can result in stress and disrupt the counselor's mental health.. Counselors need Self-Care in dealing with existing pressures to maintain the counselor's mental health. The use of therapeutic communication can be an effective way to support counselor Self-Care. This paper uses a qualitative approach with a literature review and observations to obtain research results that can help counselors in dealing with pressure.